Organizational Culture Dimensions in the Management of PM Gontor 7 Putera, Southeast Sulawesi - Syahrul Syahrul; Suryadi Suryadi (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2021)
This article aims to investigate: (1) ideas and ideals of the establishment of PM Gontor; (2) Phases of the grounding of Gontor's PM ideas; 3) Proliferation of PM Gontor as the largest pesantren corporation in Indonesia; 4) Elements of Gontor's organizational culture. Data was collected through interviews, observations, and documentation studies. Data analysis was carried out through four stages, namely: domain analysis, taxonomic analysis, compound analysis, and analysis of cultural themes. The results showed: (1) The existence of PM Gontor started with Pesantren Tegalsari ideas about the responsibility of advancing the Islamic Ummah and seeking the pleasure of Allah SWT; (2) The earthing phases of PM Gontor's ideas stretched during the founding of Old Gontor, the planting of shared values in the New Gontor era, instilling shared values through tiered education (3) The Gontor PM Proliferation is an effort to spread Gontor energy throughout Indonesia; (4) The elements of organizational culture in PM Gontor include the ideas/ideals of Tegalsari, educational strategies, shared values in the five souls, and the application of the five-term as a producer of the PM Gontor artifacts. The implication of this research is to continuously improve educational institutions by revitalizing the main dimensions of organizational culture.